RESEARCH ON EARTHQUAKES INDUCES LIQUEFACTION IN PADANG CITY - Agus Setyo Muntohar (2013)
Awareness and research on earthquake building resistant design was intensively carried out after fatal earthquakes in Indonesia in recent decades. However, less attention has been addressed on the phenomena of liquefaction since lack of ground motion information and record at the hazards area. In this paper, seismic ground response after two deadly earthquakes shocked Sumatera (Indonesia) in 2009 was evaluated based on the CPT datasets. Based upon back-calculation results, the possible ground accelerations were expected to be about 0.14g in the liquefied areas at Padang (West Sumatera). Those accelerations are likely to make 50% of sand layer liquefied and induced about 1% ground settlement.